The effect of Novamin on enamel content after bracket removal - Utari, Tita Ratya; Paryontri, Bayu Ananda; Muzayyana, Aini (Dental Journal (Majalah Kedokteran Gigi), 2025)
Background: Orthodontics is one of the dental rehabilitation treatments for malocclusion correction, such as fixed orthodontic treatment using brackets, as the use of orthodontic brackets for a prolonged period can damage the enamel. Novamin contains casein phosphopeptide-amorphous calcium phosphate (CPP-ACP), which can be used to prevent enamel erosion. Purpose: The aim of this study is to elucidate the effect of Novamin on the enamel content and microstructure surface after bracket removal. Methods: This study used 25 human premolar teeth randomly divided into five groups: I (Control); II (Biofix etching and bracket mounting); III (Biofix-Novamin); IV (Fuji Ortho); and V (Fuji Ortho-Novamin). Results: The results represent significant differences in the average levels of calcium (Ca) and phosphorus (P) among the treatment groups (p ≤ 0.05). The changes to the enamel surface indicated the opening of enamel prisms, pits, and grooves. The levels of Ca and P increased after applying Novamin, especially in groups II and III, indicating remineralization on the enamel surface. When Novamin reacts with saliva, it starts to remineralize, and sodium ions are released. The sodium ions exchange with hydrogen cations, releasing Ca and P ions from Novamin particles. Conclusion: Novamin presented the capability to stimulate remineralization after orthodontic bracket debonding through altering the Ca and P levels on the enamel surface.